Gene-ecology of durum wheat HMW glutenin reflects their diffusion from the center of origin. Issue 1 (December 2018) - Janni, M.; Cadonici, S.; Bonas, U.; Grasso, A.; Dahab, A.; Visioli, G.; Pignone, D.; Ceriotti, A.; Marmiroli, N.
Abstract The production of many food items processed from wheat grain relies on the use of high gluten strength flours. As a result, about 80% of the allelic variability in the genes encoding the glutenin proteins has been lost in the shift from landraces to modern cultivars. Here, the allelic variability in the genes encoding the high molecular weight glutenin subunits (HMW-GSs) has been characterized in 152 durum wheat lines developed from a set of landraces. The allelic composition at the twoGlu-1 loci (Glu-A1 and -B1 ) was obtained at both the protein and the DNA level. The former locus was represented by three alleles, of which the null alleleGlu-A1c was the most common. TheGlu-B1 locus was more variable, with fifteen alleles represented, of whichGlu-B1b (HMW-GSs 7 + 8), -B1d (6 + 8) and -B1e (20 + 20) were the most frequently occurring. The composition of HMW-GSs has been used to make inferences regarding the diffusion and diversification of durum wheat. The relationships of these allelic frequencies with their geographical distribution within the Mediterranean basin is discussed in terms of gene-ecology.